A Randomized Controlled Trial on Functional Relaxation as an Adjunct to Psychoeducation for Stress - Lahmann, Claas; Gebhardt, Maria; Sattel, Heribert; Dinkel, Andreas; Pieh, Christoph; Probst, Thomas (Frontiers in Psychology, 2017)
This randomized controlled trial investigated whether adding the psychodynamically based body-oriented psychotherapy “Functional Relaxation” (FR) to psychoeducation (PE) is more effective than PE alone to reduce stress and stress-associated complaints. Eighty-one participants with elevated stress-levels, ≥50 points on the global scale of the Perceived Stress Questionnaire (PSQ), received either 10 sessions of manualized FR + PE (n = 42) or two sessions of manualized PE alone (n = 39) in a group setting. Six FR trainers took part in this study. Stress-level (PSQ) was the primary outcome and secondary outcomes were depression (PHQ-9) and somatization (PHQ-15). Multilevel models for discontinuous change revealed that FR + PE was more helpful to reduce stress-levels than PE from pre-treatment to post-treatment (t0 → t1) as well as from pre-treatment to 6-month follow-up (t0 → t2) (both p < 0.05) with effect sizes (d) being medium for PE (dt0 → t1 = 0.57; dt0 → t2 = 0.67) and large for FR + PE (dt0 → t1 = 1.57; dt0 → t2 = 1.39). Moreover, FR + PE affected depression and somatization more positively than did PE from t0 to t1 as well as from t0 to t2 (all p < 0.05). Effect sizes for depression were small to medium for PE (dt0 → t1 = 0.52; dt0 → t2 = 0.37) and large for FR + PE (dt0 → t1 = 1.04; dt0 → t2 = 0.95). Effect sizes for somatization were small for PE (dt0 → t1 = 0.18; dt0 → t2 = 0.19) and medium to large for FR + PE (dt0 → t1 = 0.73; dt0 → t2 = 0.93). In summary, the combination of FR and PE was more effective than PE alone. The results of the present trial provide first evidence of FR as a potent component of stress interventions. Adding FR to such interventions might better help prevent clinically relevant disorders such as depression or somatization.